2014
DOI: 10.25269/jsel.v4i02.64
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Proses Digestasi Anaerobik Lumpur Biologi Instalasi Pengolahan Air Limbah Industri Kertas

Abstract: A continuous pilot scale study has been conducted to investigate the effectiveness of anaerobic digestion of biological sludge. The sludge has a total solid content of 0.53% - 1.1%, pH of 7.20 to 7.32. Its organic content is about 97 %, The research were conducted in two stages, which are acidification (performed in 3 m3 the Continously Stirred Tank Reactor/CSTR at pH of 5.5 to 6.0) and methanation (performed in 5 m3 the Up Flow Anaerobic Sludge Blanket/UASB reactor at pH 6.5 to 7.0). The retention time (RT) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…However, this study was conducted under a maintained temperature of 37 C, a condition that can be costly for medium-scale industries. A local study by Soetopo et al [8] showed that the highest biogas methane content from AD of PS is 51.5% at the rate of 140 ml/g VS in 28 days. Nevertheless, this study was conducted using only sludge from secondary biological wastewater treatment.…”
Section: Introductionmentioning
confidence: 98%
“…However, this study was conducted under a maintained temperature of 37 C, a condition that can be costly for medium-scale industries. A local study by Soetopo et al [8] showed that the highest biogas methane content from AD of PS is 51.5% at the rate of 140 ml/g VS in 28 days. Nevertheless, this study was conducted using only sludge from secondary biological wastewater treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Dari beberapa enzim yang digunakan pada penelitian tersebut, salah satu diantaranya yaitu protease, dapat menghasilkan produk hidrolisa yang bersifat mudah larut dan menjadi sumber nutrisi yang digunakan oleh mikroba pembentuk asam asetat. Kinerja enzim protease akan maksimal bila bekerja pada pH optimumnya 4,5-7,0 dan temperatur dengan kisaran 55-75° C (Rina, 2010) Penelitian telah dilakukan untuk mengkaji efisiensi proses digestasi anaerobik dua-tahap yang dilakukan dalam reaktor terpisah antara proses hidrolisis-asidifikasi pada reaktor pertama dan proses metanasi pada reaktor kedua. Tulisan ini melaporkan efektivitas proses hidrolisisasidifikasi dengan pengaruh adanya aplikasi protease dan suhu termofilik -mesofilik, serta beberapa variabel proses untuk menentukan kondisi operasi yang memberikan kinerja terbaik.…”
Section: Pendahuluanunclassified